Monte Carlo Simulation-Based BEAMnrc Code of a 6 MV Photon Beam Produced by a Linear Accelerator (LINAC) - R. Sapundani; R. Ekawati; K. M. Wibowo (PPIKSN-BATAN, 2021)
In radiotherapy, high energy ionizing radiation, such as X-rays, gamma rays and electron beams,is used. The dose in the tissue is often approached with the dose in the medium of the body which is 80 % of human soft tissue. It is often difficult to determine the dose because the interaction of materials in a medium is very random. Measurement is also quite difficult because there are almost no detectors that are tissue equivalent. Measurement using an ion chamber requires a lot of correction to obtain a dose in the tissue, which is done using phantom and not directly in humans. This research aimed to compare the absorbed dose between modelling using Monte Carlo simulation and experiments. The simulation of dose distribution produced by a 6 MV medical linear accelerator has been performed using BEAMnrc code running on Linux-based 2 processor system arranged in parallel.BEAMnrc was used to model and simulate the linac head with an SSD of 100 cm and Field size of10x10 cm2. A phase-space file is obtained as input to a DOSXYnrc code to produce Percent Depth Dose (PDD) in water and polymethyl methacrylate (PMMA) phantoms. New particles formed (electrons: 0.2 %, photon: 0.17 %; and positron: 0.08 %) were far from the contamination threshold of 2 %. The range of the correction factor of the depth of a maximum dose compared to the experimental data was 0.04-0.15.